(untitled) (Islas, 2023)
ABSTRACT Introduction: Aim of this article is to bring together interwoven imageries, discourses, and practices showing how they are constitutive of an archipelagic narrative of the Caribbean that is shifting to continental space. Methods: I will convey an approach in which the past is remembered as a series of fragmentary spaces, cultures, and histories that converge in a fluid space. Following Glissant, the Caribbean is reciprocally «written» resulting in a Caribbean identity as a lived experience in an archipelagic world. Results: The Caribbean islands were one of the few places of refuge for Jews fleeing the Nazi regime. Self-sufficient Jewish communities developed, and their Jewishness was entangled with the histories and memories of the islands. Drawing on descendants’ experience, I will reveal how a Caribbean narrative is defined and remembered. Conclusions: Caribbean islands act here as a space of confluences, where the Caribbean is the point where different historical imaginaries meet multidirectionally, offering a possibility to understand violent histories and their legacy in today’s world.